Intra‐cardiac echocardiography guided catheter ablation of a right posterior accessory pathway in a patient with Ebstein's anomaly. Issue 6 (20th March 2014) - Shimane, Akira; Okajima, Katsunori; Kiuchi, Kunihiko; Kanda, Gaku; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Yamada, Shinichiro; Taniguchi, Yasuyo; Kawai, Hiroya; Yasaka, Yoshinori; et al.
Abstract: We report a case of Ebstein's anomaly in which radiofrequency catheter ablation of an accessory pathway was successfully performed under intra‐cardiac echocardiography. A 50‐year‐old woman was referred to our hospital for radiofrequency catheter ablation of a paroxysmal supraventricular tachycardia. A 12‐lead surface electrocardiogram revealed ventricular pre‐excitation associated with type B Wolff–Parkinson–White syndrome. In the baseline electrophysiological study, an orthodromic atrioventricular reciprocating tachycardia with a right posterior accessory pathway was induced. A phased‐array intra‐cardiac echo probe was positioned in the right atrium to visualize the atrioventricular junction. The key structures for catheter ablation, such as the atrialized right ventricle, atrioventricular junction, and tricuspid valve, were clearly visualized on intra‐cardiac echocardiography. Radiofrequency current was successfully delivered at the atrioventricular junction, where a Kent potential was recorded. During a 6‐month follow‐up period, the patient was free from arrhythmias. The findings in this case suggest that phased‐array intra‐cardiac echocardiography is useful for ablation of right‐sided accessory pathways in patients with Ebstein's anomaly.